PENGARUH PROFITABILITAS, OPINI AUDIT DAN UMUR PERUSAHAAN TERHADAP AUDIT DELAY PADA PERUSAHAAN ASURANSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2019 -2022 - Hutapea, Jesica; Rudy (Publika Citra Media, 2024)
This research aims to analyze the influence of Audit Opinion, Company Age and Profitability on audit delay. The type of research used is quantitative research and the data source used is secondary data, namely annual financial reports obtained from the Indonesia Stock Exchange (BEI). The population in this study are insurance companies listed on the Indonesia Stock Exchange (BEI) during the 2019-2022 period. The sample selection technique in this research is purposive sampling, namely a sample selection technique based on certain considerations or criteria and the sample in this research was obtained from 8 companies over 4 years. The analytical method used in this research uses multiple linear regression analysis techniques with the help of the e-views version 9 application. Based on the results of hypothesis testing, the results of this research simultaneously influence the variables Audit Opinion, Company Age and Profitability on Audit Delay. Meanwhile, partially Audit Opinion has a significant effect on audit delay, Company Age has no significant effect on audit delay and Profitability has no significant effect on audit delay